905 Distracted walking among teens and pre-teens in U.S. and China: analysis of observations. (1st September 2016) - Gautam, Priti; Cui, Monica; Wang, Fannie; Rosenthal, Kristin; Ferguson, Rennie
Abstract : Background: To determine the level of distracted walking among teenagers and pre-teens in the U.S. and China, research examined the percentage of teenagers and pre-teens crossing the street near schools while distracted in a sample of communities in both nations. Results and focus group findings were used to develop targeted interventions. Methods: Observations were made of 34, 325 of teens and preteens crossing streets near schools in 24 communities in the U.S, and 8, 250 observations were made of teens and preteens in 8 communities in China. Data was collected near middle schools and high schools. Observers conducted two morning and afternoon sessions, on different days but held at the same time, on school days in good weather. Each observer focused on one crossing location. Students also participated in focus groups that explored attitudes and perceived risks. Results: Most frequent forms of distraction in the U.S. were texting, 39%, headphone use, 39%, and talking on phones, 20%. In China, key distractions were headphones, 42.5%, texting, 22.5%, and games, 15.8%. The odds of a girl crossing the street distracted were greater than of a boy in both countries. Differences in distraction levels were also observed when traffic lights are present and at different times of the day. During focus groups in both nations, nearly 50% of students reported cell phone use while walking to school. Teens did not perceive distraction putting them at greater risk. Findings were used to build "The Moment of Silence" Campaign, which uses social media to engage teens. Conclusions: Many teens and pre-teens are distracted while walking, but do not perceive this behaviour as risky. Targeted interventions are needed.